Development of Retail Clothing Business Strategies in Traditional Markets of Cibinong in the Post-COVID-19 Era - Lili Efnita; Ma’mun Sarma; Elisa Anggraeni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Pasar Cibinong in Bogor Regency plays a crucial role in the local economy. However, traditional market traders, particularly clothing retailers, face significant challenges in the post-COVID-19 era, including reduced consumer purchasing power and increasing competition from e-commerce platforms. This study aims to (1) identify the condition of clothing retailers during and after the COVID-19 pandemic, (2) analyze internal and external factors influencing business development, (3) formulate strategies to enhance competitiveness, and (4) determine strategic priorities. A mixed-methods approach was employed, combining qualitative and quantitative data. Qualitative data were obtained through in-depth interviews with five respondents (three clothing retailers and two market managers) and direct observation. Quantitative data were collected via questionnaires distributed to 30 consumers. SWOT analysis was used to examine internal and external factors, while the Analytical Hierarchy Process (AHP) determined strategy priorities. Findings show that COVID-19 significantly reduced retailers' incomes. Although the number of traders increased post-pandemic, consumer purchasing power remains low. Retailers benefit from strengths such as strong social interaction and flexible pricing, but struggle with limited technological adoption. SWOT analysis revealed opportunities like Pasar Cibinong’s strategic location and consumer trust, and threats from online competition. Four main strategies were formulated: Horizontal Integration of Traders, Cibinong Go Digital, Cibinong Easy Pay, and Cibinong Comfortable Shopping. AHP results ranked Cibinong Go Digital as the top priority (weight: 0.49), emphasizing digital integration and training. The implementation of Cibinong Go Digital is expected to improve competitiveness, requiring comprehensive support from market authorities and local government, alongside community participation.